The modern study of religion a preliminary survey on Clifford Geertz - Wan Mohd Fazrul Azdi Wan Razali (Penerbit Universiti Sains Islam Malaysia, 2009)
It is pertinent to understand the modern study of religion because our perception of religion today, in one way or another, has been shaep by it. Irrespective of whether the contents or finding of a study or a particular religious phenomenon reflect their actual state, these contents and finding have influenced perception of people that also include politicians and policy makers one agress with the modern methods in the study of religion, or their contents and findings, to be fimiliar with them is paramount to understand how religion has been perceived today, whether by muslims or non-muslims alike. as such, the choice of clifford geertz (1926-2006) for this writing is made based on the consideration of the interdisciplinary approach taken by geertz in the study of religion.